Refleksi Hari Pendidikan Nasional 2025 : Sekolah Rakyat dan Kurikulum Deep Learning - Maryono Maryono; Robingun Suyud El Syam; Salis Irvan Fuadi (Lembaga Pengembangan Kinerja Dosen, 2025)
The article aims to describe the reflection of National Education Day 2025 regarding the People's School and the Deep Learning Curriculum, where previous researchers have not been specific to this aspect. This research is a qualitative setting with descriptive analysis and relates it to theory. The findings show that National Education Day 2025 is a moment of deep reflection on the nature of education as a process of humanization of humans. Education is not just academic, but is a cultural means to educate the life of the nation and form an enlightened civilization. The